(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The application of nitrogen (N) in the correct dose and at the right time can favor the productivity and quality of wheat seeds. In this sense, the objective was to evaluate the effect of split nitrogen fertilization on the productivity and physiological quality of seeds of wheat cultivars. The seeds used in the experiment were produced at the National Soybean Research Center (Embrapa Soja), in Londrina-PR, in a randomized block experimental design in a 2 × 7 factorial scheme, with four replications. The treatments consisted of two cultivars and seven combinations of application of nitrogen fertilization. The following were evaluated: productivity, germination, first germination count, length and dry mass of seedlings, emergence of seedlings in sand and emergence speed index. The data were subjected to analysis of variance with comparison of means by the F test, between genotypes, and Skott-Knott, between N combinations. The effect of nitrogen fertilization on seed productivity varies with the cultivar used. For both cultivars, nitrogen fertilization applied in a single dose increases the physiological potential of seeds. The inadequate supply of N impairs the physiological quality of seeds produced.